PERAN KEPUASAN PELANGGAN, KUALITAS PELAYANAN DAN PSYCOLOGICAL CAPITAL TERHADAP LOYALITAS PELANGGAN PADA CV LADUNY ALIFATAMA - Mutmainah, Siti; Febriyanto, Febriyanto; Riyanto, Kuncoro Budi (SIMPLEX: Journal of Economic Management, 2025)
The publishing sub-sector is one of the important pillars in supporting the creative economy in Indonesia. CV Laduny Alifatama is a publishing and printing company in Metro City with more than 1,000 customers since its inception. This research examines the influence of customer satisfaction, service quality, and psycological capital on customer loyalty. The research method used is quantitative, using a probability sampling technique with a purposive sampling type, the population in this research is CV Laduny Aliftama customers in the 2018 - 2024 period of 1000 people, the number of samples was determined using the Solvin formula so that 91 respondents were obtained. The data collection technique used in this research is in the form of a questionnaire. The results of this research are (1) Customer satisfaction has a significant effect on customer loyalty at CV Laduny Alifatama. (2) Service quality has a significant effect on customer loyalty at CV Laduny Alifatama. (3) Psycological capital has a significant effect on customer loyalty at CV Laduny Alifatama. (4) Customer satisfaction, service quality, and psycological capital simultaneously have a significant effect on customer loyalty at CV Laduny Alifatama.